Paediatric intraoral mucoepidermoid carcinoma mimicking a bone lesion - PAULO MORAES, CLAUDIO PEREIRA, OSLEI ALMEIDA, DANYEL PEREZ, MARIA ELVIRA CORREA, & FABIO ALVES (IAPD and Blackwell, 2007)
Mucoepidermoid carcinoma of the salivary glands occurs most frequently in adults during the fifth and sixth decades of life. Although uncommon, it is the main malignant salivary gland tumour in children, particularly adolescents.